Advances in enzyme regulation. - Weber, George; Weber, Catherine Elizabeth Forrest (Symposium Publications Division, Pergamon Press ; Distributed in the Western Hemishpere by the Macmillan Co., 1963)
Vol. 1- Proceedings of a Symposium Regulation of Enzyme Activity and Synthesis in Normal and Neoplastic Liver, 1962-